PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN PENDAPATAN GURU TERHADAP KINERJA GURU DI SMP NEGERI SE KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Melia Nurul Huda Nurul Huda; Syakdanur Nas Syakdanur Nas; RM Riadi RM Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The performance of teachers was instrumental in realizing the ultimate goal of the school, and it's all but regardless of how the leadership and policies provided by the school principal. Performance is influenced by various factors one of which revenue and salaries. Revenues have an impact tranquility and comfort of teachers in teaching. This study aimed to analyze the influence of the leadership style of the principal and income of teachers on teacher performance in Junior High School at District of Rambah. The analytical method used is descriptive quantitative method. The survey results revealed the principal's leadership style Junior High School at District of Rambah tend to use democratic leadership style, while revenues included into the category of being a teacher and teacher performance included in either category. SPSS revenue from the test results of the most influential teachers on teacher performance in the Junior High School at District of Rambah that is t count (5,005).Keywords: Leadership, Incomes, Performance